Trilogy of birds, by Luiz Horácio - Hohlfeldt, Antonio (2024)
The article provides a panoramic but critical overview of the set of three novels by Luiz Horácio, which is called the “trilogy of birds”, highlighting the syncretism between the so-called “gauchesca” tradition and contemporary urban narrative. In the text, in addition to the syntheses of the plots, which in this case are important, some principles that organize the narrative are analyzed, relating the set of novels to varied sources of Western literature, to conclude about their affiliation with the tradition of classical literature, characterizing themselves, however, as a collectivist epic.